The in vitro biocompatibility of d-(+) raffinose modified chitosan: Two-dimensional and three-dimensional systems for culturing of horse articular chondrocytes. (December 2017) - De Angelis, Elena; Ravanetti, Francesca; Martelli, Paolo; Cacchioli, Antonio; Ivanovska, Ana; Corradi, Attilio; Nasi, Sonia; Bianchera, Annalisa; Passeri, Benedetta; Canelli, Elena; Bettini, Ruggero; Borghetti, Paolo
Abstract: The present study investigated the biocompatibility of chitosan films and scaffolds modified withd -(+)raffinose and their capability to support the growth and maintenance of the differentiation of articular chondrocytes in vitro. Primary equine articular chondrocytes were cultured on films and scaffolds of modifiedd -(+) raffinose chitosan. Their behavior was compared to that of chondrocytes grown in conventional bi- and three-dimensional culture systems, such as micromasses and alginate beads. Chitosan films maintained the phenotype of differentiated chondrocytes (typical round morphology) and sustained the synthesis of cartilaginous extracellular matrix (ECM), even at 4 weeks of culture. Indeed, starting from 2 weeks of culture, chondrocytes seeded on chitosan scaffolds were able to penetrate the surface pores and to colonize the internal matrix. Moreover they produced ECM expressing the genes of typical chondrocytes differentiation markers such as collagen II and aggrecan. In conclusion, chitosan modified withd -raffinose represents an ideal support for chondrocyte adhesion, proliferation and for the maintenance of cellular phenotypic and genotypic differentiation. This novel biomaterial could potentially be a reliable support for the re-differentiation of dedifferentiated chondrocytes. Highlights: Equine primary chondrocyte as model for test novelty chitosan film and scaffold d (+)raffinose Chitosan supports cell adhesion and ingrowth of articular chondrocytes. Proper chondrocyte morphology and ECM synthesis were observed by SEM and histology. Differentiation ECM markers of articular chondrocytes were confirmed by RT-PCR.